THEORETICAL ISSUES OF LINGUOPOETICS - Toshkhujaeva Shoirakhan G’anievna (EPRA International Journal of Research and Development (IJRD), 2022)
This article deals with issues related to the emergence of linguopoetics. The relationship between linguistics and poetics is shown.